Tia1 dependent regulation of mRNA subcellular location and translation controls p53 expression in B cells - Manuel D. Díaz-Muñoz (Nature Portfolio, 2017)
Sequestering mRNA in cytoplasmic stress granules is a mechanism for translational repression. Here the authors find that p53 mRNA, present in stress granules in activated B lymphocytes, is released upon DNA damage and is translated in a CAP-independent manner.